Separation and purification of bromelain from pineapple residue using ultrafiltration membranes: a review - Beatriz Godoi de Nogueira; Daniel Bastos de Rezende; Kátia Cecília de Souza Figueiredo (The Journal of Engineering and Exact Sciences)
Pineapple is the most popular fruit globally, whose production increased in the last years, raising concerns about the reuse of the waste. Bromelain constitutes an attractive byproduct for various industrial sectors. Ultrafiltration (UF), widely applied in macromolecule retention processes, faces significant challenges such as fouling, which limits its effectiveness. This article reviews strategies to improve permeate flow and control fouling during bromelain recovery from pineapple residues. Prominent strategies for improving UF performance include gas sparging, vibratory or rotational modules, and pre-treatment processes like diafiltration or enzymatic treatment. While gas sparging enhances turbulence and flow, its energy efficiency is limited. Integrated approaches, such as combining MF and UF or utilizing two-stage UF systems, achieve high bromelain recovery (over 94%) and effective fouling control. Strategies involving turbulence promoters enhanced permeate flux by over 40%, while fouling mitigation techniques reduced fouling rates by up to 80%, preserving enzyme activity. These findings suggest that advancements in module design, pre-treatment processes, and turbulence-inducing systems can significantly enhance UF performance, offering promising directions for industrial bromelain recovery.